Economic and social progress in Latin America : 1989 report - Inter-American Development Bank.; David Rockefeller Center for Latin American Studies (Washington, D.C. Inter-American Development Bank, 1989)
Explanation on restructuring trade through re-composition of production and export in Latin America.
Subtitle varies.
sju 22/01/2019
Loans
Keywords: Economic history; Social conditions; Agricultural development; Latin America